2005
DOI: 10.1093/ptj/85.6.515
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of a Self-report Instrument to Measure Actions: Outpatient Physical Therapy Improvement in Movement Assessment Log (OPTIMAL)

Abstract: Background and Purpose. Physical therapy is faced with the challenge of producing evidence that physical therapy interventions are effective. The fundamental question confronting physical therapy is whether or not physical therapy interventions make a contribution to function, health, and well-being. The individual's ability to perform actions can serve as a theoretical construct related to movement and health around which physical therapy interventions can be assessed. To this end, the aims of this study were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
29

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 10 publications
0
18
0
29
Order By: Relevance
“…The Outpatient Physical Therapy Improvement in Movement Assessment Log (OPTIMAL) is a self‐report instrument developed to measure the ability to perform mobility actions in the adult physical therapy population . It consists of 2 scales, difficulty and confidence, that respectively assess difficulty and confidence in performing movements.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The Outpatient Physical Therapy Improvement in Movement Assessment Log (OPTIMAL) is a self‐report instrument developed to measure the ability to perform mobility actions in the adult physical therapy population . It consists of 2 scales, difficulty and confidence, that respectively assess difficulty and confidence in performing movements.…”
Section: Introductionmentioning
confidence: 99%
“…The original study of the OPTIMAL identified 3 factors in the 2 scales: trunk mobility, lower extremity mobility, and upper extremity mobility. Cronbach α coefficients were 0.85‐0.95 in these subscales . Each scale consists of 22 items related to the mobility domain within the activities and participation component of the International Classification of Functioning, Disability and Health .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations